Survivin Promotes Piperlongumine Resistance in Ovarian Cancer - Nan, Xing-Wei; Gong, Li-Hua; Chen, Xu; Zhou, Hai-Hong; Ye, Piao-Piao; Yang, Yang; Xing, Zi-Hao; Wei, Meng-Ning; Li, Yao; Wang, Sheng-Te; Liu, Kun; Shi, Zhi; et al. (Frontiers in Oncology, 2019)
Ovarian cancer is one of the most fatal female malignancies while targeting apoptosis is critical for improving ovarian cancer patients' lives. Survivin is regarded as the most robust anti-apoptosis protein, and its overexpression in ovarian cancer is related to poor survival and apoptosis resistance. Piperlongumine (PL) extracted from peppers is defined as an active alkaloid/amide and exhibits a broad spectrum of antitumor effects. Here, we demonstrate that PL induces the rapid depletion of survivin protein levels via reactive oxygen species (ROS)-mediated proteasome-dependent pathway in vitro, while exerting a remarkable inhibitory influence on the proliferation of ovarian cancer cells. Overexpression of survivin raises the survival rate of ovarian cancer cells to PL. Moreover, PL inhibits ovarian cancer cells xenograft tumor growth and downregulates survivin in vivo. Our findings reveal a previously unrecognized mechanism of PL in suppressing survivin expression as well as survivin promotes piperlongumine resistance in ovarian cancer and suggest that ROS-mediated proteasome-dependent pathway can be exploited to overcome apoptosis resistance triggered by aberrant expression of survivin.